Applications of hydrogels and nanoparticles in the treatment of traumatic brain injury - Shi, Jiaying; Tang, Jiajia; Xu, Jin; Jiang, Ning; Yang, Yuanwei; Chen, Honglin; Han, Yuhan; Fu, Xianhua (Frontiers in Bioengineering and Biotechnology, 2025)
Traumatic brain injury (TBI) represents a significant global public health issue, with effective management posing numerous challenges. The pathophysiology of TBI is typically categorized into two phases: primary and secondary injuries. Secondary injury involves pathophysiological mechanisms such as blood-brain barrier (BBB) disruption, mitochondrial dysfunction, oxidative stress, and inflammatory responses. Current pharmacological strategies often encounter obstacles in treating TBI effectively, primarily due to challenges in BBB penetration, inadequate target site accumulation, and off-target toxicity. Versatile hydrogels and nanoparticles offer potential solutions to these limitations. This review discusses recent progress in utilizing hydrogels and nanoparticles for TBI treatment over the past 5 years, highlighting their relevance to the underlying injury pathophysiology. Hydrogels and nanoparticles demonstrate substantial promise in addressing secondary brain injury, providing a broad spectrum of future therapeutic opportunities.